Aquatic habitats in sustainable urban water management science, policy and practice - Wagner, Iwona 1971-; Marsalek, J. (Jiri) 1940-; Breil, Pascal; International Hydrological Programme; UNESCO (Paris UNESCO, 2008)
Aquatic habitats supply a wide range of vital ecosystem benefits to cities and their inhabitants. The unsustainable use of aquatic habitats, including inadequate urban water management, however, tends to alter and reduce their biodiversity and thereby diminish their ability to provide clean water, protect humans from waterborne diseases and pollutants, keep urban areas safe from flooding, and support recreational ecosystem services and even aesthetic enjoyment. This publication aims at improving understanding of aquatic habitats, related ecosystem goods and services, and conservation and sustainable use, with a special focus on their integration into urban water management.
Introduction to urban aquatic habitat management -- Urban aquatic habitats : characteristics and functioning -- Strategies, policies and regulations integrating protection and rehabilitation of aquatic habitats in urban water management -- Ecosensitive approaches to managing urban aquatic habitats and their integration with urban infrastructure -- Aquatic habitat rehabilitation : goals, contraints and techniques -- Ecohydrology of urban ecosystems for healthy cities -- Integrating aquatic habitat management into urban planning -- Human health and safety related to urban aquatic habitats -- Integrated management of urban aquatic habitats to enhance quality of life and environment in cities : selected case studies.
Includes bibliographical references and index.
Keywords: Aquatic habitats -- Management; Ecohydrology; Municipal water supply -- Management